2017
DOI: 10.5301/ejo.5001000
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold micropulse laser reduces anti-VEGF injection burden in patients with diabetic macular edema

Abstract: Micropulse laser is a safe and effective treatment for DME, which may achieve comparable improvement in VA along with a significant reduction in the burden of anti-VEGF injections. We suggest a treatment approach for its inclusion in the early stages of DME.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 29 publications
2
55
0
5
Order By: Relevance
“…Additionally, a recent study retrospectively included 38 eyes with DME to either subthreshold diode micropulse photocoagulation or 3 loading doses of intravitreal injections with ranibizumab. Comparable results in regards to VA were found in both groups but with a significantly lower need for intravitreal ranibizumab in the laser group during 12 months follow-up (Moisseiev et al 2017).…”
Section: Subthreshold Diode Micropulse Laser Photocoagulationmentioning
confidence: 64%
See 1 more Smart Citation
“…Additionally, a recent study retrospectively included 38 eyes with DME to either subthreshold diode micropulse photocoagulation or 3 loading doses of intravitreal injections with ranibizumab. Comparable results in regards to VA were found in both groups but with a significantly lower need for intravitreal ranibizumab in the laser group during 12 months follow-up (Moisseiev et al 2017).…”
Section: Subthreshold Diode Micropulse Laser Photocoagulationmentioning
confidence: 64%
“…Comparable results in regards to VA were found in both groups but with a significantly lower need for intravitreal ranibizumab in the laser group during 12 months follow‐up (Moisseiev et al. ).…”
Section: Laser Systemsmentioning
confidence: 89%
“…The use of a subthreshold laser for the treatment of DME patients is known to lead to better results in terms of effectiveness and safety than conventional laser photocoagulation [13]. It might also decrease the injection burden in these patients [14]. In our study, a yellow subthreshold laser applied with a fovea-sparing technique with 1/3 power titration was shown to be a safe and effective treatment for CI-DME in patients presenting with good VA.…”
Section: Discussionmentioning
confidence: 57%
“…A recent retrospective study of Moiseiev et al could also show a significant reduction in the burden of anti-VEGF injections when combining with MPL for DME treatment [ 22 ]. Kanar et al demonstrated in a randomized clinical trial, that combining intravitreal aflibercept injections with subthreshold micropulse yellow laser for DME treatment results in fewer intravitreal injections and similar anatomic and functional outcome [ 23 ].…”
Section: Discussionmentioning
confidence: 99%